A speech enhancement improvement in communication through hearing protection device - Selamat, 'Atiqah; Razali, Ailin; Tang, Howe Hing (IIUM Press, International Islamic University Malaysia, 2017)
This book is written with the main purpose to distribute the knowledge ofone of the many studies made about enhancing speech enhancement in communication among those workers who wear hearing protection devices (HPD) as part of the Hearing Conservation Programme (HCP). A HCP may be as important as if no other engineering approach or from the management side is impractical, therefore the HPD must be worn whenever and wherever required. Nowadays, there are so many HPD like the earmuff that provide the user to protect their hearing if said properly worn. Some of the HPDs have the feature that allowing the speech of a worker to be understood by the other whom wear HPD that block out unnecessary noise. In the engineering approach, many researchers have study about many methods to achieve the communication while HPD worn. In addition, the importance of the communication at noisy workplace is that it may give warning indicator and clear instruction. In the public health perspective, wearing a HPD is a method to reduce the occurrence of occupational Noise Induced Hearing Loss (NIHL). However, HPD usage is not liked at all time or for all workers, thus they tend to not use the device accordingly. One of the reason is the user cannot make good communication while wearing HPD. It is hopefully, through the written content of this book, people would have a better option of HPD with appropriate communication feature by continuing previous researches made.